2016
DOI: 10.7717/peerj.1946
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the beta-diversity of spider communities in northwestern Argentinean Grasslands

Abstract: Beta-diversity, defined as spatial replacement in species composition, is crucial to the understanding of how local communities assemble. These changes can be driven by environmental or geographic factors (such as geographic distance), or a combination of the two. Spiders have been shown to be good indicators of environmental quality. Accordingly, spiders are used in this work as model taxa to establish whether there is a decrease in community similarity that corresponds to geographic distance in the grassland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 59 publications
0
29
1
4
Order By: Relevance
“…al. 2009, Rodriguez et al 2016. Asimismo, la estimación de especies fue superior a la obtenida en gran parte de dichos sitios con el mismo estimador.…”
Section: Resultados Y Discusión Diversidad Alfaunclassified
See 2 more Smart Citations
“…al. 2009, Rodriguez et al 2016. Asimismo, la estimación de especies fue superior a la obtenida en gran parte de dichos sitios con el mismo estimador.…”
Section: Resultados Y Discusión Diversidad Alfaunclassified
“…Por otra parte, hay estudios que demuestran que los ensambles de arañas fluctúan en función de la complejidad estructural del hábitat (Uetz 1991, Malumbres-O et al 2013, Rodriguez-A et al 2016) y de los parámetros físicos, como temperatura, precipitaciones y humedad (Ziesche y Roth 2008, Rubio y Acosta 2011, Rodriguez-A et al 2016). La relevancia de estos factores depende de la estacionalidad, por lo que otro factor a tener en cuenta en los estudios ecológicos son las estaciones climáticas (Ziesche y Roth 2008).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Spiders have their diversity dependent of many factors (Foelix, 2011): vegetal structure (Baldissera et al, 2004;Nogueira & Pinto-da-Rocha, 2016), capacity of dispersal and settlement (Rodrigues et al, 2009;Lin et al, 2016) being distance insignificant (Horváth et al, 2009), prey availability and competitive exclusion (Dennis et al, 2015;Rodriguez-Artigas et al, 2016). Moreover, spider are still capable of consume high biomass rate (Nyfeller, 2000;Ott, 2016), are generalist predators in different trophic levels, even eating other spiders (Wise, 2006) and occupying nearly all terrestrial territories (Foelix, 2011), making up great ecological models (Craig et al, 2001;Foelix, 2011).…”
mentioning
confidence: 99%
“…In this sense, variation in local habitat structure is associated with changes in spider assemblage composition (Tews et al ., ; Jiménez‐Valverde & Lobo, ; Carvalho et al ., ; Ávila et al ., ). Previous studies revealed that climate is another important driver of spider distribution on a broader scale (Jiménez‐Valverde & Lobo, ; Finch et al ., ; Jiménez‐Valverde et al ., ; Carvalho et al ., ; Rodriguez‐Artigas et al ., ).…”
Section: Introductionmentioning
confidence: 97%